2015
DOI: 10.1002/nop2.16
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y New Zealand Registered Nurses’ views about nursing work: a survey of motivation and maintenance factors

Abstract: AimThe aim of this article was to report on the analysis of qualitative, open text data, received from a national on‐line survey of what factors Generation Y New Zealand Registered Nurses wish to change about nursing and consideration of the potential policy and practice impacts of these requests on their retention.BackgroundPrior to the economic recession of 2007–2010, the growing shortage of nurses in New Zealand presented a serious concern for the healthcare workforce. Given the ageing New Zealand nursing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…As temporary arrangements increase the likelihood of temporary employees developing transactional rather than relational interactions with their employers (Van Breugel et al, ), nurses' experience of work time shapes the way they relate to their colleagues and vice versa. For instance, although nursing researchers have studied mentoring extensively and have reported that Millennial nurses in particular want ongoing mentoring and flexible careers (Hale, ; Jamieson, Kirk, Wright, & Andrew, ), the nursing scholarship sheds limited light on how alternative work arrangements affect mentoring as a communicative behaviour (Gan, ). As Millennial nurses will have increasingly diverse nursing career options (Jamieson et al, ), researchers should invest greater effort into understanding Millennial nurses' thoughts about alternative work arrangements.…”
Section: Resultsmentioning
confidence: 99%
“…As temporary arrangements increase the likelihood of temporary employees developing transactional rather than relational interactions with their employers (Van Breugel et al, ), nurses' experience of work time shapes the way they relate to their colleagues and vice versa. For instance, although nursing researchers have studied mentoring extensively and have reported that Millennial nurses in particular want ongoing mentoring and flexible careers (Hale, ; Jamieson, Kirk, Wright, & Andrew, ), the nursing scholarship sheds limited light on how alternative work arrangements affect mentoring as a communicative behaviour (Gan, ). As Millennial nurses will have increasingly diverse nursing career options (Jamieson et al, ), researchers should invest greater effort into understanding Millennial nurses' thoughts about alternative work arrangements.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from international nursing studies describe the generation Y as dissatisfied, who expect better working conditions (Jamieson, Kirk, Wright, & Andrew, ; Wilson, Squires, Widger, Cranley, & Tourangeau, ) and are less resilient than generation X and baby boomers (Hakim, ). Some research has identified generation‐dependent variables for the generations Y, X and baby boomers concerning their wishes to stay in the nursing work force (Shacklock & Brunetto, ; Tourangeau, Thomson, Cummings, & Cranley, ).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies on generation‐specific human resource management in the care sector have been conducted mostly in Australia, New Zealand and the United States (Anselmo‐Witzel, Orshan, Heitner, & Bachand, ; Christensen et al, ; Farr‐Wharton, Brunetto, & Shacklock, ; Jamieson et al, ; Sherman, ). Since no study has yet been conducted on the different generations' attitudes about working in health care and nursing in Germany, the present study sought to close this research gap and contribute to the discussion on managing according to specific generation characteristics in an international context.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, nurses who exhibit benevolent behaviours are reported to have high motivation (Koch, Proynova, Paech, & Wetter, ). Additionally, a study conducted on Generation Y nurses, it was stated that improving the working conditions and relations between peers, both of which are among Herzberg's maintenance factors, and stopping negative attitudes and bullying were essential (Jamieson, Kirk, Wright, & Andrew, ). In today's health care system, respectful and collegial communication is essential (Cowin & Eagar, ) and nurses are expected to be reliable colleagues and team members in their organisational roles.…”
Section: Discussionmentioning
confidence: 99%